Does Job Satisfaction Lead to Consideration and Personal Sensitivity? - Motowidlo, Stephan J. (Academy of Management Journal, 1984)
The article discusses research pertaining to the relationships between job satisfaction and other behavioral patterns related to altruism and consideration at the workplace. Job satisfaction was measured by a 10-item instrument that asked how satisfied people were with aspects of the job such as pay, kind of work, supervisor, co-workers, and the company as a whole. The sample of participants included 79 managers who took part in a training program and 77 others who had not yet taken part in it. Further analyses were conducted to determine whether correlations with supervisory ratings might vary for different aspects of satisfaction included in the overall measure. Feelings of satisfaction were associated with patterns of behavior at work that reflect interpersonal sensitivity and kindness.